2022
DOI: 10.3390/biomedicines10102619
|View full text |Cite
|
Sign up to set email alerts
|

Non Coding RNAs as Regulators of Wnt/β-Catenin and Hippo Pathways in Arrhythmogenic Cardiomyopathy

Abstract: Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiomyopathy histologically characterized by the replacement of myocardium by fibrofatty infiltration, cardiomyocyte loss, and inflammation. ACM has been defined as a desmosomal disease because most of the mutations causing the disease are located in genes encoding desmosomal proteins. Interestingly, the instable structures of these intercellular junctions in this disease are closely related to a perturbed Wnt/β-catenin pathway. Imbalance in the Wnt/β-caten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Piquer-Gil et al ( Piquer-Gil et al, 2022 ) also reported that axes such as lncRNA UCA1/miR-18a/YAP and lncRNA FLVCR1-AS1/miR-513/YAP promote YAP activity through miRNA inhibition. In addition, there may be a bidirectional relationship between YAP/TAZ and ncRNA.…”
Section: Non-coding Rna/hippo Pathway In Cardiac Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Piquer-Gil et al ( Piquer-Gil et al, 2022 ) also reported that axes such as lncRNA UCA1/miR-18a/YAP and lncRNA FLVCR1-AS1/miR-513/YAP promote YAP activity through miRNA inhibition. In addition, there may be a bidirectional relationship between YAP/TAZ and ncRNA.…”
Section: Non-coding Rna/hippo Pathway In Cardiac Diseasesmentioning
confidence: 99%
“…For example, YAP and lncRNA RP11-323N12.5 can bidirectionally regulate the activities of both genes, thereby promoting the expression of genes regulated by YAP. However, the role of these targets in heart disease need to be further investigated ( Piquer-Gil et al, 2022 ).…”
Section: Non-coding Rna/hippo Pathway In Cardiac Diseasesmentioning
confidence: 99%
“…For instance, Leavy et al [24] reported that the impairment of normal brain maturation caused by early life brain injury (such as hypoxia) is accompanied by modification of miRNA expression, possibly driven by cMYC. In their review, Piquer-Gil et al [25] focused on the importance of the balance between two key pathways (Wnt/β-catenin and Hippo pathways) in the progression of the pathological arrhythmogenic cardiomyopathy (ACM) phenotype, a form of heart disease that can cause sudden death. The authors, by using data from cancer research, hypothesized that non-coding RNA (including miRNAs) could play a role in regulating these pathways in ACM.…”
Section: Mirnas In Human Diseasesmentioning
confidence: 99%
“…For example, the miR-145-5p and miR-585-3p are associated with the standing position of Brugada patients, which might be the potential utility of leucocyte-derived miRNAs as prognostic biomarkers for Brugada syndrome [ 31 , 32 ]. Arrhythmogenic cardiomyopathy is a genetically determined disorder caused by mutations in proteins constituting desmosomes, which might be an inherited cardiomyopathy histologically categorized by the replacement of myocardium with inflammation, fibrofatty infiltration, and cardiomyocyte loss [ 33 ]. Inflammation might also be involved in the pathogenesis of arrhythmogenic cardiomyopathy with various inflammatory cytokines [ 34 ].…”
Section: Other Cardiac Rhythm Disordersmentioning
confidence: 99%